Terrorism And Its Socio-Economic Impact On Pakistan: A Critical Analysis - Muhammad Shehzad Khan Niazi; Abrar Ahmad; Syed Tajammul Abbas, (Dialogue Social Science Review (DSSR), 2025)
Terrorism has posed a persistent threat to Pakistan’s socio-economic development over the past two decades. This study critically examines the multifaceted impact of terrorism on Pakistan’s economy and social fabric. It explores in what way frequent terrorist incidents have disrupted economic activities, reduced foreign direct investment (FDI), increased security expenditures, and weakened the overall investment climate. The paper further investigates the social consequences, including psychological trauma, displacement of communities, erosion of public trust in institutions, and the deterioration of educational and healthcare services in conflict-affected regions. The study also evaluates government policies and counterterrorism strategies, assessing their effectiveness in mitigating the long-term damage to economic growth and social cohesion. Finally, the paper proposes a multi-dimensional policy framework emphasizing inclusive development, education reform, and institutional strengthening as key to addressing the root causes of terrorism. This critical analysis contributes to a deeper understanding of terrorism’s pervasive impact on Pakistan and underscores the need for comprehensive, sustainable responses to restore stability and development. Keywords: Terrorism, Socio-economic impact, Pakistan, Security and development, Counterterrorism policy